Using Biotechnology to Create Transgenic Crops that Resist Climate Change - Gusti Rusmayadi (CV. Get Press Indonesia, 2024)
Climate change is a major threat to food security, especially for farmers in vulnerable areas facing the challenges of climate change. This study aimed to modify the plant genome to increase tolerance to extreme climatic conditions such as drought and high temperatures using genetic engineering methods based on CRISPR-Cas9 technology. Transgenic and control plants were grown in a laboratory experimental design with a quantitative approach. The results showed that the transgenic plants consistently outperformed the control plants under drought, high temperature, and low nutrient conditions. The transgenic plant showed a growth rate of 15.2 and average productivity of 25.7, higher than the control (12.3 and 19.1). Under high temperature conditions, the increase in productivity was even greater, reaching 33.2%, indicating that the inserted HSP gene successfully protects important proteins from heat stress damage. Genetic modification through the expression of genes such as DREB1A, HSP70, and PHR1 was shown to increase plant resistance to environmental stress. With these findings, biotechnology provides a real opportunity to build more adaptive and sustainable agricultural systems, supporting global food needs amid the intensifying challenges of global warming. This research is very relevant in answering the big challenge in the future, which is how to ensure biotechnology can be utilised sustainably to meet the world's growing food needs, without compromising ecosystems and biodiversity.